Structure et caractéristiques de la flore adventice de la ferme agricole de l’Université Gaston Berger de Saint-Louis (Sénégal) - César, Bassene; Nicolas, Mansaly; Rahimi, Mballo; Aziz, Camara Abdoul; Samba, Mbaye Mame; Kandioura, Noba (European Scientific Journal, ESJ, 2018)
This present study was conducted to determine the structure and characteristics of the adventitious flora of the agricultural farm of Gaston Berger University (UGB) located in Saint Louis, Senegal. A species inventory was carried out using the "tour de champ" technique which consists of going through a plot in different directions and recording all the species present in the studied area. The inventoried flora is composed of 149 species distributed among 90 genera belonging to 30 families which are dominated by the Poaceae (18.8%) and the Fabaceae (15.4%). This flora is also characterized by the predominance of the therophytes and the chamephytes which represent 79.9% and 10.7% of recorded species, respectively. From a chorologic standpoint, pantropical (29.5%) and African (28.2%) species account for more than half of the species (57.7%). The quantitative analysis of this flora reveals that rare or accidental species are more represented (52%) followed by frequent species (16%) and secondary species (15%).